How Improving the Resilience of Special Education School Teachers in Forming Students’ Positive Characters? - Anggraeni, Femia Dwita; Rahmatullah, Azam Syukur (FKIP Universitas Lampung, 2025)
How Improving the Resilience of Special Education School Teachers in Forming Students’ Positive Characters. This research aims to determine and analyze the process of improving the resilience of special education school teachers in forming positive characters of students at SLB Negeri 1 Bantul Yogyakarta. In addition, this research is also to determine the forms of improving the resilience of teachers at SLB Negeri 1 Bantul Yogyakarta, and to determine the supporting and inhibiting factors of the process of improving the resilience of the special education school teachers in forming positive character of students at the school. The research approach used is a phenomenological study. The research subjects were determined by the researcher along with recommendations from SLB Negeri 1 Bantul Yogyakarta. The data were collected using data collection techniques in the form of observation, interviews, and documentation. The data obtained were analyzed using phenomenological study data analysis techniques. The results show that the longer the teacher work and teach the students with special needs, the more comfortable and loving the teachers are with their jobs. This is indicating the process of self-resilience improvement. To form this self-resilience, the teachers need to perform several efforts, one of them is by pursuing divine connection with God Almighty, this is proven to lighten their workload. The supporting factors in the process of improving the resilience of teachers at SLB Negeri 1 Bantul Yogyakarta are the teachers themselves, students, and social support. Meanwhile, the inhibiting factors are the students and their parents. Keywords: self-resilience, special education schools, positive characters.